2018
DOI: 10.1016/j.jcat.2017.12.028
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of the electrochemical conversion of ammonia to dinitrogen on Pt(1 0 0) in alkaline environment

Abstract: The electrochemical oxidation of ammonia to dinitrogen is a model reaction for the electrocatalysis of the nitrogen cycle, as it can contribute to the understanding of the making/breaking of N-N, NO , or N-H bonds. Moreover, it can be used as the anode reaction in ammonia electrolyzers for H2 production or in ammonia fuel cells. We study here the reaction on the N2-forming Pt(100) electrode using a combination of electrochemical methods, product characterization and computational methods, and suggest a mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
129
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(136 citation statements)
references
References 59 publications
6
129
1
Order By: Relevance
“…The complete dehydrogenation of ammonia yields the Nads species which is inert for the formation of N2, but in kinetics it was considered as a catalytic poison [78]. The essence of the Gerischer-Mauerer mechanism has been corroborated [79,80] Studies employing Pt basal planes, namely, the Pt(111), Pt(110) and Pt(100), in alkaline media, showed that the electrochemical oxidation reaction of ammonia is extremely structure sensitive and takes place almost exclusively on sites with (100) symmetry [82]. In line with this statement, different voltammetric profiles for ammonia electro-oxidation on Pt basal planes, in alkaline solution, are displayed in Figure 8.…”
Section: Electro-oxidation Of Ammoniamentioning
confidence: 99%
See 1 more Smart Citation
“…The complete dehydrogenation of ammonia yields the Nads species which is inert for the formation of N2, but in kinetics it was considered as a catalytic poison [78]. The essence of the Gerischer-Mauerer mechanism has been corroborated [79,80] Studies employing Pt basal planes, namely, the Pt(111), Pt(110) and Pt(100), in alkaline media, showed that the electrochemical oxidation reaction of ammonia is extremely structure sensitive and takes place almost exclusively on sites with (100) symmetry [82]. In line with this statement, different voltammetric profiles for ammonia electro-oxidation on Pt basal planes, in alkaline solution, are displayed in Figure 8.…”
Section: Electro-oxidation Of Ammoniamentioning
confidence: 99%
“…The electrochemical reduction of nitrite (NO 2 − ) toward N2 is another electrocatalytic reaction that preferentially takes place on the (100) facet of the Pt [86], whose reaction mechanism (in terms of intermediates of reactions) has been claimed has some similarity with oxidation mechanism of NH3 to N2 [87]. Returning to the reaction mechanism of ammonia electro-oxidation on Pt(100) in alkaline media, recently, Katsounaros et al [80] proposed that the dimerization of NH, ads species to N2H2, ads ones, being the last of which is dehydrogenated to N2; and the Nads species serves as a reaction intermediate for the formation of byproducts as is the NOads species. Both Nads and NOads acting as catalyst poisons.…”
Section: Electro-oxidation Of Ammoniamentioning
confidence: 99%
“…Combined with the electrochemical behaviors in CV curves, both of the ammonia oxidation and nitrite selective reduction to N2 on the exposed Pt(100) terraces in such nanostructured Pt NFs covered with a small amount of Cu contribute to the generation of N2. The major electrochemical reactions involved in the nitrate electroreduction are proposed in the Scheme 1 [35,36,38]. Detailed pathways of nitrate reduction on Cu / Pt NFs / CC will be further studied in the future.…”
Section: Assessment Of Cu Sites and Coverage On Cu/pt Nfs/ccmentioning
confidence: 99%
“…Many efforts have been devoted to removing NH 3 from gaseous and waste streams through chemical, biological, and physical methods, but all have their limitations [2][3][4]. Recently, electrocatalytic oxidation of ammonia (AEO) has attracted much attention of researchers and scientists because, as a hydrogen-rich carrier, it possesses 70% higher volumetric hydrogen content than pure liquid hydrogen [5,6]. Theoretical and experimental investigations reveal that hydrogen generation via ammonia electro-oxidation (AEO) is a cost-effective approach compared to water electrolysis because it requires much lower oxidation potential (0.06 V) than water (−1.23 V), as described in Equations (1-3) [7,8].…”
Section: Introductionmentioning
confidence: 99%